Potassium Based Calcium Oxide Catalyst Synthesis for Efficient Transesterification of Waste Cooking Oil - Bushra Hassan (00000206368); Dr Rabia Liaquat (USPCAS-E, NUST, Islamabad, 2021)
TH-286
Keywords: MS-TEE Thesis